FROM TRADITIONAL TO DIGITAL: DIGITAL TRANSFORMATION STRATEGY FOR MICRO AND SMALL BUSINESSES IN THE STREET FOOD SECTOR IN THE CITY OF BANDUNG - Adrian Ariatin; Imanuddin Hasbi (ITB AAS Indonesia Surakarta, 2026)
Digital transformation has become an important strategy for micro and small enterprises (MSEs) to increase competitiveness in the digital economy era. However, many micro business actors still face various challenges in adopting digital technology, especially related to digital literacy, limited resources, and understanding of digital marketing strategies. This study aims to analyze the digital transformation process in micro and small businesses in the street food sector in Bandung, a city known as one of Indonesia's culinary destinations with high street food diversity. This study uses a qualitative case study approach. The research data were obtained from students' field assignments in the digital entrepreneurship course, in which students conducted observations and semi-structured interviews with micro-business actors to identify problems related to digital business transformation. The data were analyzed using a thematic analysis to identify problem patterns and digital transformation strategies that emerged from various micro-business cases. The study's results show that most business actors still rely on traditional methods such as word-of-mouth promotion and direct sales. Some businesses have begun adopting digital technologies such as social media, instant messaging, and digital payments, but their use remains partial and has not been integrated into a comprehensive business strategy. This study also found that student involvement through project-based learning can act as a catalyst in digitizing micro businesses. This study contributes to the literature on digital transformation in micro enterprises by highlighting the importance of digital literacy, digital marketing strategies, and collaboration between universities and local business actors in supporting the business transformation process towards a digital ecosystem.